The king's deception ebook - Berry, Steve (Cotton Malone, 2013)
NEW YORK TIMES BESTSELLER • This Cotton Malone adventure blends gripping contemporary political intrigue, Tudor treachery, and high-octane thrills into one riveting novel of suspense.   Cotton Malone and his fifteen-year-old son, Gary, are headed to Europe. As a favor to his former boss at the Justice Department, Malone agrees to escort a teenage fugitive back to England. But after he is greeted at gunpoint in London, both the fugitive and Gary disappear, and Malone learns that he’s stumbled into a high-stakes diplomatic showdown—an international incident fueled by geopolitical gamesmanship and shocking Tudor secrets.   At its heart is the Libyan terrorist convicted of bombing Pan Am Flight 103, who is set to be released by Scottish authorities for “humanitarian reasons.” An outraged American government objects, but nothing can persuade the British to intervene.   Except, perhaps, Operation King’s Deception.   Run by the CIA, the operation aims to solve a centuries-old mystery, one that could rock Great Britain to its royal foundations.   Blake Antrim, the CIA operative in charge of King’s Deception, is hunting for the spark that could rekindle a most dangerous fire, the one thing that every Irish national has sought for generations: a legal reason why the English must leave Northern Ireland. The answer is a long-buried secret that calls into question the legitimacy of the entire forty-five-year reign of Elizabeth I, the last Tudor monarch, who completed the conquest of Ireland and seized much of its land. But Antrim also has a more personal agenda, a twisted game of revenge in which Gary is a pawn. With assassins, traitors, spies, and dangerous disciples of a secret society closing in, Malone is caught in a lethal bind. To save Gary he must play one treacherous player against another—and only by uncovering the incredible truth can he hope to prevent the shattering consequences of the King’s Deception. Don’t miss Steve Berry’s novella The Tudor Plot and an excerpt from  The Lincoln Myth  in the back of the book. Praise for The King’s Deception   “A Dan Brown-ian secular conspiracy about the Virgin Queen driving nonstop international intrigue.” —Kirkus Reviews Praise for Steve Berry   “Berry raises this genre’s stakes.”— The New York Times   “I love this guy.”—#1 New York Times bestselling author Lee Child   “Forget Clancy and Cussler. When it comes to this genre, there is simply no one better.” —The Providence Journal